Comparing the prophylaxis effect of Ondansetron and Metoclopramide against intraoperative nausea and vomiting during spinal anesthesia for cesarean section - H Zahedi (Babol University of Medical Sciences, 2004)
Background and Objective: Nausea and vomiting are complications of cesarean section (C/S) during spinal anesthesia and different methods have been suggested to prevent it. The aim of this study was to compare incidence of intraoperative nausea and vomiting (IONV) during cesarean section (S/C) under spinal anesthesia. Methods: This double-blind and placebo-controlled study was performed on 150 ASA 1;2 women submitted for spinal anesthesia scheduled C/S. They were divided into three groups: 4mg ondansetron, 10mg metoclopramide or saline were administered I.V after clamping of umbilical cord, depending on their treatment group. After that treatment, if INOV appeared or the patients had no subside completely after 5 minutes, the subjects were treated with droperidol. Findings: Nausea and vomiting were not seen in 91.8% of the ondansetron group, 91.6% of the metoclopramide group and 60% of the placebo group (P<0.001). There was no significant difference between the first and second groups. Emetic symptoms were more frequent after clamping the umbilical cord (25.9%) than prior to it (16.3%) (P<0.05). Conclusion: According to the results, there was no significant difference between ondansetron and metoclopramide. For reducing IONV, it is recommended to use metoclopramide for preventing intraoperative nausea vomiting during spinal anesthesia for C/S.